(untitled) (New York, 1990)
Mosaic Two: A Listening/Speaking Skills Book, 3/e, teaches learning strategies and language functions, while maintaining a strong focus on both listening and speaking. Each chapter teaches one learning strategy and one language function within the context of the chapter theme. Ideal for high-intermediate to low-advanced students.
Keywords: English language,English language; Conversation and phrase books,Textbooks for foreign speakers